Nutritional Potential of the Invasive Charru Mussel (Mytella strigata): A Focus on Fatty Acid Composition for Aquaculture Feed Applications - Kutako, Maliwan; Siranonthana, Nisa; Watanachote, Janjarus (Journal of Food Health and Bioenvironmental Science, 2024)
The charru mussel, Mytella strigata (Hanley, 1843), is an invasive alien species of mussel reported in Thai waters. Originally native to Central and South America, it now poses an economic risk to commercial mussel farming in Thailand, as it commonly co-occurs with the cultured species Perna viridis and exhibits a remarkable tolerance to a wide range of salinities and temperatures. While its geographic distribution in Thailand is well-documented and it is occasionally sold in domestic markets—indicating potential as an alternative protein source for humans or animals—there is limited information regarding its nutritional composition. Therefore, investigating the nutritional properties of M. strigata is essential to assess its suitability as an alternative food source. The objectives of this study were to determine the nutritional content of M. strigata and evaluate its potential as an alternative food source for humans or animals. Samples of M. strigata were collected from Klongdan, Samut Prakan Province. Thirty individuals were selected for the measurement of shell length and width, along with their total weight and wet meat weight. The meat yield was calculated. The wet meat was then dried for proximate analysis and fatty acid analysis. The results found that M. strigata had a shell width of 13.6 ± 0.62 mm and a shell length of 43.2 ± 1.19 mm. Their total weight and wet meat weight were 5.22 ± 0.20 g and 1.47 ± 041 g, respectively. The meat yield was 33.3 ± 9.36%. The wet meat exhibited the following composition: moisture (81.4±0.6%), protein (6.65±1.6%), lipid (1.13±0.2%), and ash (0.45±0.1%). The fatty acid composition showed the highest percentage in saturated fatty acids (31.47 ± 1.79% of total fatty acids, TFA), followed by polyunsaturated fatty acids (PUFAs) (23.73 ± 0.38% TFA) and monounsaturated fatty acids (MUFAs) (17.18 ± 0.77% TFA). Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) accounted for 8.71 ± 0.08% and 7.83 ± 0.16% TFA, respectively. In conclusion, M. strigata demonstrates potential as a nutritious food source for humans, owing to its high protein content and favorable n-3/n-6 PUFA ratio. Additionally, its nutritional profile supports its use as an alternative feed source for aquatic animals, such as fish and shrimp.